Orientation relationships, interface structures, and mechanical properties of directionally solidified MoSi2/Mo5Si3/Mo5Si3C composites. (June 2016) - Matsunoshita, Hirotaka; Fujiwara, Kosuke; Sasai, Yuta; Kishida, Kyosuke; Inui, Haruyuki
Abstract: The microstructures, orientation relationships, and high-temperature deformation behavior of directionally solidified (DS) ingots of MoSi2 /Mo5 Si3 /Mo5 Si3 C three-phase eutectic composites were investigated. The DS three-phase composites exhibit a fine and homogeneous script lamellar microstructure. Mo5 Si3 and Mo5 Si3 C individually form interconnected networks that extend in the growth direction (GD) of the MoSi2 matrix and maintain [ 1 1 ¯ 0 ] MoSi 2, [ 001 ] Mo 5 Si 3, and [ 0001 ] Mo 5 Si 3 C approximately parallel to the GD. High-temperature strength is higher in the DS three-phase composite than in the binary two-phase counterpart, especially below 1200 °C. This is mainly because of MoSi2 matrix refinement and the presence of the strengthening phase Mo5 Si3 C. The observed orientation relationship between component phases is discussed in relation to lattice misfits. Highlights: DS MoSi2 /Mo5 Si3 /Mo5 Si3 C composites exhibit a fine script lamellar microstructure. Mo5 Si3 C forms interconnected networks and divides MoSi2 matrix into small regions. The orientation relationship is selected to effectively accommodate lattice misfits. Three-phase composites have higher yield strength than two-phase counterpart.